Pengaruh Citra, Kualitas Makanan Dan Atmosphere Terhadap Keputusan Pembelian Pada Warung Mina Peguyangan Di Denpasar - Apriyanti, Ni Wayan; Putu Kawiana, I Gusti; Agustina, Made Dian Putri (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Purchasing decision is a process of making a purchase decision which includes a decision to buy or not. The purpose of this study was to determine the effect of image, food quality and atmosphere on purchasing decisions either partially or simultaneously. This research was conducted at Warung Mina Peguyangan Denpasar. The number of samples taken as many as 100 people and tested using multiple linear regression analysis techniques. Based on the results of the analysis, it was found that image, food quality and atmosphere had a positive and significant effect on purchasing decisions. Suggestions that can be given to Warung Mina Peguyangan is that it is hoped that the management can build a good impression in the minds of consumers, pay attention to the temperature of the food served to match the type of menu offered, and be more effective in arranging tables and chairs so that consumers are comfortable when shopping.